The contribution of economic intelligence to the firm performance - Amine Ben Hadj Hassine (Quantitative Economics and Management Studies, 2021)
To the extent that the company is an “open system”, it must be in a continuous standby state. In this research work, we will try to focus on the contribution of economic intelligence strategies to the performance of the company. We will begin with a literature review to better understand the theoretical concepts. Then we will conduct a field study of 92 Tunisian industrial companies. Our work has revealed that economic intelligence has a positive but differential effect on the firm’s performance. But some determinants of performance do not seem to take full advantage of the strategies of economic intelligence to which companies should attach greater importance.